The shock doctrine : the rise of disaster capitalism - Klein, Naomi, 1970- (New York : Picador, 2007)
In this groundbreaking alternative history of the most dominant ideology of our time, Milton Friedman's free-market economic revolution, Naomi Klein challenges the popular myth of this movement's peaceful global victory. From Chile in 1973 to Iraq today, Klein shows how Friedman and his followers have repeatedly harnessed terrible shocks and violence to implement their radical policies
Introduction : blank is beautiful : three decades of erasing and remaking the world -- The torture lab : Ewen Cameron, the CIA and the maniacal quest to erase and remake the human mind -- The other Doctor Shock : Milton Friedman and the search for a laissez-faire laboratory -- States of shock : the bloody birth of the counter-revolution -- Cleaning the slate : terror does its work -- "Entirely unrelated" : how an ideology was cleansed of its crimes -- Saved by a war : Thatcherism and its useful enemies -- The new Dr. Shock : economic warfare replaces dictatorship -- Crisis works : the packaging of shock therapy -- Slamming the door on history : a crisis in Poland, a massacre in China -- Democracy born in chains : South Africa's constricted freedom -- Bonfire of a young democracy : Russia chooses "the Pinochet option" -- The capitalist ID : Russia and the new era of the boor market -- Let it burn : the looting of Asia and "the fall of the second Berlin Wall" -- Shock therapy in the U.S.A. : the Homeland security bubble -- A corporatist state : removing the revolving door, putting in an archway -- Erasing Iraq : in search of a "model" for the Middle East -- Ideological blowback : a very capitalist disaster -- Full circle : from blank slate to scorched earth -- Blanking the beach : "the second tsunami" -- Disaster apartheid : a world of green zones and red zones -- Losing the peace incentive : Israel as warning -- Conclusion : shock wears off : the rise of people's reconstruction
Includes bibliographical references and index
Keywords: Free enterprise; Financial crises; Capitalism